Results of orthodontic treatment young patients with edentulous permanent teeth - Filimonov В. Ю.; Alekseyenko Н. В.; Lavreniuk Я. В.; Kovach І. В. (Actual Dentistry, 2022)
Аdentia has a negative effect on the development of the dentition, and the absence of the first molars creates conditions for a progressive decrease in the height of the bite, which does not lend itself to self-regulation and leads to disruption of the functioning of other organs of the dentoalveolar system and the occurrence of complications. Orthodontic closure of dental arch defects restores the integrity of the dentition and improves the functioning of the dentition as a whole. The aim of this work was to study the results of orthodontic treatment of young patients with edentulous permanent teeth using microimplants. According to the results of the treatment of 17 patients with edentulous teeth with the actually developed orthodontic method using microimplants, positive results were obtained regarding molar protraction, which is faster than using the conventional method and the rotation of mesial teeth arising from molar protraction is leveled.